[Hagadah shel Pesaḥ] [be-ʻIvrit ṿe-ʻAravit-Yehudit]. - Hebrew Manuscripts (Columbia University Libraries) ([Place of publication not identified])
The order of the Passover Haggadah according to the Oriental rite. The text includes the Hebrew text, followed by a Judeo- Arabic translation of the text.
Manuscript written on paper in Oriental cursive handwriting.
Also available on microfilm.
Electronic reproduction.
Mode of access: Internet.
Benchmark for Faithful Digital Reproductions of Monographs and Serials. Version 1. December 2002.
Vocalized Hebrew
Keywords: Haggadah -- 19th century; Manuscripts, Hebrew -- 19th century; Jewish religious poetry, Hebrew -- 19th century; Hebrew poetry -- 19th century; Judeo-Arabic literature -- 19th century; Passover -- Liturgy -- Texts -- 19th century; Manuscripts, Hebrew -- 19th century